Gene therapy in cardiomyopathies - Review of the latest reports - Strzelczyk, Magdalena; Pabis, Gabriela; Wziątek , Joanna; Bętkowska , Paula; Koziołek , Iwona; Kowalik , Piotr; Fatyga , Patrycja; Fatyga , Wiktoria; Krzyżanowska , Daria; Dowierciał , Kinga (Quality in Sport, 2025)
Introduction and purpose Gene therapy appears to be a promising treatment for patients with cardiomyopathy and innovative therapeutic option. The aim of this review is to present the latest gene therapy technologies, innovations, research in the treatment of cardiomyopathy and analysis of the ethical issues associated with the use of modern therapies. Material and methods This review is based on recent articles from the years 2020-2025 found in databases such PubMed, Elsevier. Results Gene editing through CRISPR-Cas technology allows for the modification of genetic material by making changes at precise locations what is highly useful in gene therapy. Gene Expression Regulation (RNAi) involves preventing the production of proteins by silencing a faulty gene. Antisense therapy (ASO) uses antisense oligonucleotides to exclude a particular exon and causes the translation process to stop. Gene replacement involves introducing a healthy copy of a mutated gene into the genome along with an appropriate vector. Conclusions Individual technologies in the treatment of cardiomyopathy show potential for treating patients in the future. It is also important to remember the ethical issues when using solutions based on gene therapy. Clinical trials in the future are necessary to further search for solutions for patients with cardiomyopathy.